Role of Flexible Cystoscopy and Ultrasound Together in the Detection of Recurrent Superficial Bladder Tumors; A Comparison With Rigid Cystoscopy (Bangladesh Journal of Urology, 2020)
Objective: To evaluate the role of flexible cystoscopy and ultrasound together in thedetection of recurrent superficial bladder tumorsMethod: This hospital based prospective comparative study was carried out in theDepartment of Urology, National Institute of Kidney Diseases and Urology, Sher-E-Banglanagar, Dhaka from January 2013 to June 2014. A total of 85 patients of post transurethralresection (TUR) and post chemotherapy state for superficial bladder tumors were includedin this study. Transabdominal ultrasonography of the bladder was performed for all casesby a consultant radiologist. Flexible cystoscopy was performed by a trained urologist forall. Finally conventional rigid cystoscopy with or without biopsy was performed at thesame setting to confirmed the findings.Result:The mean age was found 62.9±9.7 years with range from 41 to 80 years. Majority(82.4%) patients were male and 15(17.6%) patients were female. Male female ratio was4.7:1. It was observed that majority (54.1%) patients was found pT1 stage and 39(45.9%)was pTa stage. It was observed that more than two third (67.1%) patients had grade-Iand 28(32.9%) had grade-II.Sensitivity, specificity, accuracy, positive and negativepredictive values of combine USG and flexible cystoscopy for identification of recurrenttumors were 92.7%, 33.3%, 90.6%, 97.4% and 14.3%.Conclusion: Ultrasonography and flexible cytoscopy together can detect recurrentsuperficial bladder tumors as accurate as conventional rigid cytoscopy.Bangladesh Journal of Urology, Vol. 22, No. 1, January 2019 p.41-46